On-tree ripening block of avocado fruit involves changes in ethylene sensitivity linked to gibberellin and auxin pathways - Donald A. Hunter; Kristie O’Donnell; Huaibi Zhang; Zoe A. Erridge; Nathanael J. Napier; Paul Pidakala; Ellen Baylis; Ali Saei; Catrin Günther; Janine M. Cooney; Charles David; Benjamin Franzmayr; et al. (Postharvest Biology and Technology, 2024)

Feasibility and Tolerability of Daily Microgreen Consumption in Healthy Middle-Aged/Older Adults: A Randomized Crossover Trial - S. Holmes; K. Michell; M. Butler; B. Smith; A. Vazquez; E. Woolf; L. Grabos; S. Lee; S. Newman; M. Uchanski; T. Weir; S. Johnson (Journal of the Academy of Nutrition and Dietetics, 2023)

Ocean carbon from space: Current status and priorities for the next decade - Robert J.W. Brewin; Shubha Sathyendranath; Gemma Kulk; Marie-Hélène Rio; Javier A. Concha; Thomas G. Bell; Astrid Bracher; Cédric Fichot; Thomas L. Frölicher; Martí Galí; Dennis Arthur Hansell; Tihomir S. Kostadinov; et al. (Earth-Science Reviews, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The FluxEngine air–sea gas flux toolbox: simplified interface and extensions for in situ analyses and multiple sparingly soluble gases - Thomas Holding; Ian G. Ashton; Jamie D. Shutler; Peter E. Land; Philip D. Nightingale; Andrew P. Rees; Ian Brown; Jean-Francois Piolle; Annette Kock; Hermann W. Bange; David K. Woolf; Lonneke Goddijn-Murphy; et al. (Ocean Science, 2019)
The flow (flux) of climate-critical gases, such as carbon dioxide (CO2), between the ocean and the atmosphere is a fundamental component of our climate and an important driver of the biogeochemical systems within the oceans. Therefore, the accurate calculation of these air–sea gas fluxes is critical if we are to monitor the oceans and assess the impact that these gases are having on Earth's climate and ecosystems. FluxEngine is an open-source software toolbox that allows users to easily perform calculations of air–sea gas fluxes from model, in situ, and Earth observation data. The original development and verification of the toolbox was described in a previous publication. The toolbox has now been considerably updated to allow for its use as a Python library, to enable simplified installation, to ensure verification of its installation, to enable the handling of multiple sparingly soluble gases, and to enable the greatly expanded functionality for supporting in situ dataset analyses. This new functionality for supporting in situ analyses includes user-defined grids, time periods and projections, the ability to reanalyse in situ CO2 data to a common temperature dataset, and the ability to easily calculate gas fluxes using in situ data from drifting buoys, fixed moorings, and research cruises. Here we describe these new capabilities and demonstrate their application through illustrative case studies. The first case study demonstrates the workflow for accurately calculating CO2 fluxes using in situ data from four research cruises from the Surface Ocean CO2 ATlas (SOCAT) database. The second case study calculates air–sea CO2 fluxes using in situ data from a fixed monitoring station in the Baltic Sea. The third case study focuses on nitrous oxide (N2O) and, through a user-defined gas transfer parameterisation, identifies that biological surfactants in the North Atlantic could suppress individual N2O sea–air gas fluxes by up to 13 %. The fourth and final case study illustrates how a dissipation-based gas transfer parameterisation can be implemented and used. The updated version of the toolbox (version 3) and all documentation is now freely available.

The OceanFlux Greenhouse Gases methodology for deriving a sea surface climatology of CO 2 fugacity in support of air–sea gas flux studies - L. M. Goddijn-Murphy; D. K. Woolf; P. E. Land; J. D. Shutler; C. Donlon (Ocean Science, 2015)
Climatologies, or long-term averages, of essential climate variables are useful for evaluating models and providing a baseline for studying anomalies. The Surface Ocean CO2 Atlas (SOCAT) has made millions of global underway sea surface measurements of CO2 publicly available, all in a uniform format and presented as fugacity, fCO2. As fCO2 is highly sensitive to temperature, the measurements are only valid for the instantaneous sea surface temperature (SST) that is measured concurrently with the in-water CO2 measurement. To create a climatology of fCO2 data suitable for calculating air–sea CO2 fluxes, it is therefore desirable to calculate fCO2 valid for a more consistent and averaged SST. This paper presents the OceanFlux Greenhouse Gases methodology for creating such a climatology. We recomputed SOCAT's fCO2 values for their respective measurement month and year using monthly composite SST data on a 1° × 1° grid from satellite Earth observation and then extrapolated the resulting fCO2 values to reference year 2010. The data were then spatially interpolated onto a 1° × 1° grid of the global oceans to produce 12 monthly fCO2 distributions for 2010, including the prediction errors of fCO2 produced by the spatial interpolation technique. The partial pressure of CO2 (pCO2) is also provided for those who prefer to use pCO2. The CO2 concentration difference between ocean and atmosphere is the thermodynamic driving force of the air–sea CO2 flux, and hence the presented fCO2 distributions can be used in air–sea gas flux calculations together with climatologies of other climate variables.

Workshop Report: Crystal City V—Quantitative Bioanalytical Method Validation and Implementation: The 2013 Revised FDA Guidance - Brian Booth; Mark E. Arnold; Binodh DeSilva; Lakshmi Amaravadi; Sherri Dudal; Eric Fluhler; Boris Gorovits; Sam H. Haidar; John Kadavil; Steve Lowes; Robert Nicholson; Marie Rock; et al. (The AAPS Journal, 2015)

Potato notes - Lou D. Sweet; J. H. Woolf; A. E. Wilkinson; F. C. Gaylord; E. A. Stodyke; R. D. Hews; H. C. Moore; J. W. Weston; W. V. Longley; J. Norton Woodruff; W. H. Martin; J. C. Crissey; et al. (American Journal of Potato Research, 1924)